2012
DOI: 10.1097/tp.0b013e31823ef335
|View full text |Cite
|
Sign up to set email alerts
|

Ischemic Postconditioning Protects Liver From Ischemia-Reperfusion Injury by Modulating Mitochondrial Permeability Transition

Abstract: iPoC attenuated cell deaths after I/R injury of liver. The protective effects were negated by the addition of ATR--a mPTP opener--and mimicked by injection of NIM811--a mPTP opening inhibitor. The study indicated iPoC conferred protection by modulating mPTP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
29
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 26 publications
1
29
0
Order By: Relevance
“…53 Opening of the mitochondrial permeability transition pore in liver cells was inhibited by delayed ischaemic postconditioning. 49 It is possible that the reduction in mitochondrial swelling may be due to a lowering of cytosolic Ca 2þ concentrations and inhibition of the opening of mitochondrial permeability transition pore.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…53 Opening of the mitochondrial permeability transition pore in liver cells was inhibited by delayed ischaemic postconditioning. 49 It is possible that the reduction in mitochondrial swelling may be due to a lowering of cytosolic Ca 2þ concentrations and inhibition of the opening of mitochondrial permeability transition pore.…”
Section: Discussionmentioning
confidence: 99%
“…48 In contrast, the present study found that ischaemic postconditioning significantly attenuated mitochondria swelling induced by lethal ischaemia and reperfusion. Mitochondrial swelling is related to the opening of the mitochondrial permeability transition pore, 49 with calcium ion (Ca 2þ ) concentration being proportional to the extent of pore opening. 50,51 Overload of Ca 2þ is a pathological characteristic of ischaemia/reperfusion.…”
Section: Discussionmentioning
confidence: 99%
“…Although the mechanisms responsible for ischemic PostC of the liver are not fully understood, some studies have shown that the two processes have many similarities [6][7][8]. Recent studies have demonstrated that some agents, such as adenosine A2A receptor agonist [8], rhEPO [9], and sevoflurane [10], can be used as pharmacological inducers of PostC as well as PreC.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, recent studies have proved that several brief cycles of ischemia and reperfusion at the onset of sustained reperfusion after ischemia, termed ischemic postconditioning (PostC), provided protective effects against hepatic IR injury [5][6][7]. PostC is more likely than PreC to be feasible for clinical application because the onset of reperfusion is more predictable.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation